2015
DOI: 10.1177/0022034515602478
|View full text |Cite
|
Sign up to set email alerts
|

Dental Occlusal Changes Induce Motor Cortex Neuroplasticity

Abstract: Modification to the dental occlusion may alter oral sensorimotor functions. Restorative treatments aim to restore sensorimotor functions; however, it is unclear why some patients fail to adapt to the restoration and remain with sensorimotor complaints. The face primary motor cortex (face-M1) is involved in the generation and control of orofacial movements. Altered sensory inputs or motor function can induce face-M1 neuroplasticity. We took advantage of the continuous eruption of the incisors in Sprague-Dawley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…The cortical neuroplastic changes have also been associated with the altered stomatognathic system for, for example, tooth loss, intraoral pain or nerve injury. Previous studies in rodents have suggested that the reorganisation of the MI may occur after peripheral nerve injuries . Further, experimental studies in humans have shown that manipulation of peripheral sensory inputs from oro‐facial structures alters the cortical excitability of the oro‐facial muscles …”
Section: Oral Motor Skill Acquisition and Training‐induced Neuroplastmentioning
confidence: 99%
“…The cortical neuroplastic changes have also been associated with the altered stomatognathic system for, for example, tooth loss, intraoral pain or nerve injury. Previous studies in rodents have suggested that the reorganisation of the MI may occur after peripheral nerve injuries . Further, experimental studies in humans have shown that manipulation of peripheral sensory inputs from oro‐facial structures alters the cortical excitability of the oro‐facial muscles …”
Section: Oral Motor Skill Acquisition and Training‐induced Neuroplastmentioning
confidence: 99%
“…Should one or more “musicians” (teeth) change their function or become absent, the orchestra's overall harmony will be affected, creating temporary or long‐term dissonances and increasing mental and physical stress [36]. To adapt to alterations, cope with stress, and maintain the effectiveness of the eating‐mastication function when facing such changes, it is necessary have related sensory cortical and motor reorganization [1–4]. This “symphony” can also be orchestrated by different organ systems such as mastication‐related muscles, different sensory organs, the temporal‐mandibular joint (TMJ), and the autonomic nervous system.…”
Section: Dentition and Mastication: The Correlation Between Tooth Losmentioning
confidence: 99%
“…Unlike most other types of peripheral deafferentations, DDs may develop as a frequently recurring event of significant quantity, such as multiple teeth loss at different periods of time, in various locations, and in different dental arches. After persistent occurrences of DDs, the masticatory apparatus (including TMJs, all related masticatory musculatures, as well as associated musculatures such as supra‐ and infra‐hyoid groups of muscles) may also be affected peripherally and centrally [2–4].…”
Section: The Unique Characteristics Of Multiple Recurrent Ddsmentioning
confidence: 99%
See 2 more Smart Citations